Computer graphics with OpenGL - Hearn, Donald
Reflecting the rapid expansion of the use of computer graphics and of C++ as a programming language of choice for implementation, this book converts all programming code into the C++ language. This new edition is a complete revision, bringing the text up to date with current advances in computer graphics technology and applications. Assuming readers have no prior familiarity with computer graphics, the authorsboth authorities in their fieldpresent basic principles for design, use, and understanding of computer graphics systems using their well-known, and accessible writing style. It includes an exploration of GL, PHIGS, PHIGS+, GKS and other graphics libraries and covers topics such as distributed ray tracing, radiosity, physically based modeling, particle systems, and visualization techniques. For professionals in any area of computer graphics: CAD, Animation, Software Design, etc